Single-Cell RNA Sequencing and Quantitative Proteomics Analysis Elucidate Marker Genes and Molecular Mechanisms in Hypoplastic Left Heart Patients With Heart Failure - Ma, Li; Zhou, Na; Zou, Rongjun; Shi, Wanting; Luo, Yuanyuan; Du, Na; Zhong, Jing; Zhao, Xiaodong; Chen, Xinxin; Xia, Huimin; Wu, Yueheng (Frontiers in Cell and Developmental Biology, 2021)
Objective: To probe into specifically expressed markers and molecular mechanisms of hypoplastic left heart syndrome (HLHS) by single-cell RNA sequencing (scRNA-seq) and quantitative proteomics analysis. Methods: Following data preprocessing, scRNA-seq data of pluripotent stem cells (iPSCs)-derived cardiomyocytes derived from one HLHS patient and one control were analyzed by the Seurat package in R. Cell clusters were characterized, followed by Pseudotime analysis. Markers in the Pseudotime analysis were utilized for functional enrichment analysis. Quantitative proteomics analysis was presented based on the peripheral blood samples from HLHS patients without heart failure (HLHS-NHF), HLHS with heart failure (HLHS-HF), and healthy control. Hub genes were identified by the intersection of Pseudotime markers and differentially expressed proteins (DE-proteins), which were validated in the GSE77798 dataset, RT-qPCR and western blot. Results: Cardiomyocytes derived from iPSCs were clustered into mesenchyma stem cells, myocardium, and fibroblast cell. Pseudotime analysis revealed their differentiation trajectory. Markers in the three Pseudotime clusters were significantly associated with distinct biological processes and pathways. Finally, three hub genes (MMP2, B2M, and COL5A1) were identified. They were highly expressed in the left ventricle (LV) and right ventricle (RV) HLHS compared to controls. Furthermore, their higher expression levels were detected in HLHS with or without HF than controls. Conclusion: Our findings elucidate marker genes and molecular mechanisms of HLHS, which deepen the understanding of the pathogenesis of HLHS.